Implementasi Manajemen Aplikasi Siaga Dalam Meningkatkan Kualitas Pelayanan Seksi Pais di Kantor Kemenag Surabaya - Isnaini Safitri; Vivi Desi Damayanti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
This study aims to describe the single application (information system and administration of religious teachers) to improve the quality of service for PAI teachers in the Ministry of Religion office in Surabaya. This study used the descriptive qualitative method. The subjects in this study were the kindergarten, elementary, junior high, and high school PAI teachers in the city of Surabaya. After doing this research, it can be concluded that the standby application is able to improve the service quality of the pais section in the city of the Ministry of Religion Surabaya.